Numerical investigation on heat transfer enhancement in a double pipe heat exchanger using rod inserts and nanofluids - Nfawa, Sadeq Rashid (2016)
In recent years, research on the methods for heat transfer enhancement in heat exchangers have received great attention in order to cater for the growing needs of higher efficiencies in these devices. For this purpose, double pipe heat exchanger with inserts devices is one of the many suitable techniques to enhance the heat transfer in heat exchangers. When fluid flows in a pipe with rod inserts fitted on the inner wall of the pipe, the flow becomes disturbed due to growing re-circulation regions near the pipe wall, which enhances the mixing of fluid as well as heat transfer. On the coolant side, the use of nanofluids (a liquid in which nanoparticles are added to a base fluid) can also enhance the heat transfer due to the improved thermal conductivity of the fluid. The objectives of the present investigation are to improve the thermal performance of double pipe heat exchanger by using compound of vortex generator and nanofluids simultaneously. Different angles of vortex generators were examined. Four types of nanoparticles were investigated. Several solid particle diameters and concentrations were covered. Constant nanofluid properties and single- phase models were numerically considered. A wide range of Reynolds number has been studied to cover the turbulent flow regimes. The results were subjected to Performance Evaluation Criteria to show their superiority. Numerical simulations have been achieved on wide parameters of forced convection heat transfer and nanofluids flow characteristics in the circular pipe by using turbulators protrusions namely, rod inserts of vortex generator. The rod inserts were attached on the inner wall of the test pipe while the wall was directly heated by using constant wall temperature of constant heat flux boundary conditions. The effects of four different slant angles of rod inserts (α=20o, 25°, 35°, 45°) with different of Reynold numbers from 7,500 -20,000 on the flow and thermal fields are presented and analyzed. Four different types of nanoparticles, Al2O3, CuO, SiO2, and ZnO with different volume fractions in the range of 0% to 4 % and different nanoparticle diameters in the range of 20nm to 60nm, dispersed in a base fluid (water) were used. Comparisons of the numerical results with those available in the literature have been presented and a good agreement between the results is observed. The value of performance evaluation criterion (PEC) lies in the range of 1.74-2.82, which demonstrates that the rods strip insert has a very good thermo-hydraulic performance. From the numerical results, it is clearly seen that the heat transfer with rod inserts was higher than smooth tube. Results show that the average Nusselt number, heat transfer enhancement, pressure drop, as well as the thermal hydraulic performance increase with higher values of slant angle. The circular pipe with (α=45°) rod insert provides the highest thermal- hydraulic performance at amplitudes of 7500 and 20000 of Reynolds numbers. A dramatic enhancement in Nusselt number obtained by using rod inserts of vortex generator and base fluid compared to the plane tube. Maximum enhancement of Nusselt number is about 174% by using rod inserts compared to the plane tube with water. The maximum skin friction coefficient has been found by using rod inserts in the tube at (α=45°) and pitch distance (S = 30mm). The maximum value of the (PEC) was found in the case of the lowest slant angle of (α =20o) and the pitch distance of S=30mm. Results presented show that the average Nusselt number, heat transfer enhancement, pressure drop as well as the thermal-hydraulic performance increase with higher nanoparticle volume fraction and with smaller diameter of nanoparticles. Furthermore, the SiO2 water nanofluid provides the best thermal hydraulic performance followed by Al2O3, ZnO and CuO water nanofluids. The average Nusselt number and pressure drop in the circular pipe with different shapes significantly increase, as the Reynolds number increases. About 7.5 % enhancement in the heat transfer rate were observed for SiO2-water nanofluid with 4% volume fraction and 20 nm particles diameter compared to the CuO-water nanofluid at the same volume fraction and particles diameter.